Improving the behavioral realism of global integrated assessment models: An application to consumers' vehicle choices. (August 2017) - McCollum, David L.; Wilson, Charlie; Pettifor, Hazel; Ramea, Kalai; Krey, Volker; Riahi, Keywan; Bertram, Christoph; Lin, Zhenhong; Edelenbosch, Oreane Y.; Fujisawa, Sei
Highlights: Empirical evidence shows that vehicle purchase decisions are often non-rational. Consumer heterogeneity and behavior is key for modeling a future energy transition. We describe an innovative approach for modeling vehicle choices in global IAMs. The approach considers vehicle novelty, range, refueling availability, and variety. IAMs considering heterogeneity/behavior can examine a more diverse suite of policies. Abstract: A large body of transport sector-focused research recognizes the complexity of human behavior in relation to mobility. Yet, global integrated assessment models (IAMs), which are widely used to evaluate the costs, potentials, and consequences of different greenhouse gas emission trajectories over the medium-to-long term, typically represent behavior and the end use of energy as a simple rational choice between available alternatives, even though abundant empirical evidence shows that real-world decision making is more complex and less routinely rational. This paper demonstrates the value of incorporating certain features of consumer behavior in IAMs, focusing on light-duty vehicle (LDV) purchase decisions. An innovative model formulation is developed to represent heterogeneous consumer groups with varying preferences for vehicle novelty, range, refueling/recharging availability, and variety. The formulation is then implemented in the transport module of MESSAGE-Transport, a global IAM, although it also has the generic flexibility to be applied in energy-economy models with varying set-ups. Comparison of conventional and 'behaviorally-realistic' model runs with respect to vehicle purchase decisions shows that consumer preferences may slow down the transition to alternative fuel (low-carbon) vehicles. Consequently, stronger price-based incentives and/or non-price based measures may be needed to transform the global fleet of passenger vehicles, at least in the initial market phases of novel alternatives. Otherwise, the mitigation burden borne by other transport sub-sectors and other energy sectors could be higher than previously estimated. More generally, capturing behavioral features of energy consumers in global IAMs increases their usefulness to policy makers by allowing a more realistic assessment of a more diverse suite of policies.